2016
DOI: 10.1111/anu.12438
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the arachidonic acid/vitamin E interaction on the immune response of juvenile Atlantic salmon (Salmo salar) challenged againstPiscirickettsia salmonis

Abstract: Atlantic salmon (Salmo salar) were fed 6 experimental diets containing three levels of arachidonic acid (ARA) (0.18 g kg−1, 0.28 g kg−1 and 0.63 g kg−1 for low, medium and high levels, respectively) and two levels of vitamin E (150 and 730 mg kg−1 for low and high levels, respectively). At the end of the experimental period, fatty acids in the liver and immunity markers (lysozyme activity, respiratory burst and phagocytic activity) were determined and fish subjected to a challenge test against the salmonid ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 44 publications
3
16
0
Order By: Relevance
“…An increase in lysozyme activity, along with enhanced survival, was recorded in our earlier study with guppy fry that were fed with artemia enriched in WT L. incisa ( 14 ). Furthermore, enhanced lysozyme activity with ARA-suplemented diets is documented in recent studies on rabbitfish, Atlantic salmon and grass carp ( 15 , 31 , 45 ). Lysozyme activity is an important index of innate imunity in fish and is well recognized as a useful indicator of fish health ( 46 ).…”
Section: Discussionmentioning
confidence: 88%
“…An increase in lysozyme activity, along with enhanced survival, was recorded in our earlier study with guppy fry that were fed with artemia enriched in WT L. incisa ( 14 ). Furthermore, enhanced lysozyme activity with ARA-suplemented diets is documented in recent studies on rabbitfish, Atlantic salmon and grass carp ( 15 , 31 , 45 ). Lysozyme activity is an important index of innate imunity in fish and is well recognized as a useful indicator of fish health ( 46 ).…”
Section: Discussionmentioning
confidence: 88%
“…Ash content was determined by combustion at 600ºC for 12h. Fatty acid methyl esters profiles were prepared by transmethylation (Christie 2003) and separated by gas chromatography (GC-14A, Shimadzu, Japan) following the conditions described by Izquierdo et al (1992). Fatty acid methyl esters quantification was performed by a flame ionizator detector and identification by comparison with external and well-characterized fish oils standards (EPA 28, Nippai, Ltd Tokyo, Japan).…”
Section: Proximate Composition and Fatty Acid Analysesmentioning
confidence: 99%
“…Activated macrophages secrete cytokines such as TNF-α, IL-1β and IL-6 [ 37 39 ] to defend against intracellular pathogens [ 40 ]. Normally, n-6 fatty acid plays an important role in pro-inflammatory processes by stimulating the production of pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6) [ 16 , 17 , 41 ]. The current results showed that most of the immune-associated genes were significantly enhanced with the supplementation of ARA, compared to treatment of Codium alone ( Fig 3 ), suggesting that ARA helped Codium to increase the expression of immune-associated genes in RAW264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acids are classified as saturated, monounsaturated, or polyunsaturated fatty acids (PUFA) by their degree of saturation. PUFAs such as dihomo-gamma-linolenic acid (DGLA), arachidonic acid (ARA, 20:4n-6) and eicosapentaenoic acid (EPA, 20:5n-3) are the precursors of eicosanoids which include prostaglandins (PG), thromboxanes (TX), lipoxins (LX), and leukotrienes (LT) [16,17]. These compounds are associated with the host defense system against infections including resistance to stress stimuli, the immune response, and inflammatory processes [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation